2021
DOI: 10.3390/jcm10112322
|View full text |Cite
|
Sign up to set email alerts
|

Day-Time Declamping Is Associated with Better Outcomes in Kidney Transplantation: The Circarein Study

Abstract: Despite improvements in organ preservation techniques and efforts to minimize the duration of cold ischemia, ischemia–reperfusion (IR) injury remains associated with poor graft function and long-term survival in kidney transplantation. We recently demonstrated a clinically significant day-time variation in myocardial tolerance to IR, transcriptionally orchestrated by the circadian clock. Patient and graft post-transplant survival were studied in a cohort of 10,291 patients first transplanted between 2006 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…During transplantation, the time at which the donor kidney is reperfused by the recipient’s blood is termed the allograft reperfusion time. This time has been linked to adverse outcomes during transplantation ( 25 ). A sinusoidal oscillation was observed for mean PER3 expression when the expression levels were plotted against time after allograft reperfusion ( r 2 = 0.9, P < 0.01; Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During transplantation, the time at which the donor kidney is reperfused by the recipient’s blood is termed the allograft reperfusion time. This time has been linked to adverse outcomes during transplantation ( 25 ). A sinusoidal oscillation was observed for mean PER3 expression when the expression levels were plotted against time after allograft reperfusion ( r 2 = 0.9, P < 0.01; Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…In our program, glucocorticoids are given around the time of allograft reperfusion, potentially explaining the observed phase shift in the molecular oscillator. These phase shifts have adverse consequences in a number of studies ( 9 ) and therefore could explain why renal transplant outcomes show diurnal variation at one year ( 25 ) and why, in another study, DGF oscillated in a diurnal manner ( 39 ). Our study now extends this time-of-day variation for DGF, showing that this variation is circadian.…”
Section: Discussionmentioning
confidence: 99%
“…Echoing these sentiments, Fechner et al scrutinized a dataset comprising 260 kidney transplant recipients and identified an increased risk of reoperation, particularly due to vascular complications following nighttime procedures, alongside an elevated risk of graft failure [25]. Montaigne et al presented evidence suggesting that renal transplants benefit from daytime declamping, noting improved post-transplant survival rates that held irrespective of ischemia time and other confounders [59].…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies did not observe the difference of time-of-day on outcomes, it may be due to the disorder of preoperative biological rhythm in patients with ESRF (Ville, et al, 2021) (Treacy, et al, 2022) (Sugünes, et al, 2019) (Guerrero, et al, 2021). Meanwhile, the latest cohort study with 10291 patients observed that compared to nocturnal declamping, day-time declamping was associated with a better prognosis of kidney transplantation despite a longer duration of cold ischemia (Montaigne, et al, 2021). Similarly, our previous studies have con rmed that bilateral occlusion IR model established at nighttime induced graver renal injury regarding that circadian rhythm of clock genes, and Nrf2 accumulation were a novel endogenous mechanism in renal IRI and repair processes (Sun, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, renal transplantation can only temporarily improve a series of symptoms caused by circadian rhythm disorder, but the long-term syndromes still exist (Mendoza-Romo-Ramírez, et al, 2021) (Pisano, et al, 2021). Meanwhile, the latest cohort study with 10291 patients observed that compared to nocturnal de-clamping, day-time de-clamping was associated with a better prognosis of kidney transplantation despite a longer duration of cold ischemia (Montaigne, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%